High c-Myb Expression Associates with Good Prognosis in Colorectal Carcinoma - Tichý, Michal; Knopfová, Lucia; Jarkovský, Jiří; Vlček, Petr; Katolická, Jana; Čapov, Ivan; Hermanová, Markéta; Šmarda, Jan; Beneš, Petr (Journal of Cancer, 2019)
Colorectal cancer (CRC) represents a serious challenge for oncologists due to high incidence and large heterogeneity. Prognostic factors are needed to stratify patients according to risk of disease progression. In this study, we report that high expression of c-Myb protein, determined by immunohistochemistry (IHC), associates with better overall and disease-free survival (OS, DFS) in a cohort of 103 patients. Although MYB has been previously considered to act as oncogene in CRC, our further analysis of datasets deposited in PrognoScan and SurvExpress databases confirmed that high MYB expression largely associates with good prognosis in CRC. As therapies targeting c-Myb have been developed and tested in preclinical studies, we believe that further studies are needed for detailed understanding of c-Myb function in CRC, before the c-Myb-targeted therapy enters clinical trials.
Keywords: survival; prognosis; c-Myb; colorectal cancer